Peran Business Process Management dalam Meningkatkan Daya Saing Bisnis di Pasar Global - Jeni Susyanti; Habib Nur Ahmad (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
In the era of globalization which is marked by increasingly tight business competition, companies are required to have a sustainable competitive advantage. Business Process Management (BPM) is a managerial approach that focuses on increasing the efficiency, effectiveness and flexibility of business processes to achieve organizational strategic goals. This article aims to analyze the role of BPM in increasing business competitiveness in the global market. Through literature reviews and case studies on multinational companies, it was found that consistent implementation of BPM can improve operational performance, accelerate innovation, and improve customer satisfaction. The research results show that BPM plays an important role in building competitive advantages that are adaptive to global market dynamics.